Penerapan Reverse Engineering pada Analisa Tegangan Bracket Engine Mounting - Sholikin Sholikin; Carolus Bintoro (Journal of Mechanical Engineering and Mechatronics, 2016)
Abstract. The objective of reverse engineering process in the manufacturing field is to reproduce or re-create an existing model. There are three stages in the research process: data acquisition, 3D modeling and design analysis. The results of the data capture acquisition form 3D products in .stl format. From this data is making 3D models, the level of deviation from the geometry created showing the quality of the results of the 3D bracket. The deviation was -0.8 mm in cross section runner. Geometry 3D design bracket and then analyzed using the finite element method software. For material testing bracket using the spectrometer, the type of material is aluminum AC4CH. The results of stress analysis testing in the bracket indicates there is high stress concentration at the center of the bracket. It demonstrates that the bracket will crack with the application of F 44.1 kN.Keywords. Reverse Engineering, Bracket Engine Mounting, 3D Model, CAE, CAM.